Magnetic resonance imaging characteristics and survival outcomes of metaplastic breast carcinoma - Wen-Pei Wu; Joseph Lin; Yu-Len Huang; Shou-Tung Chen; Chen-Te Chou; Dar-Ren Chen (PLoS ONE, 2025)
Objective Metaplastic breast carcinoma is a rare type of breast carcinoma, and there are limited data about the magnetic resonance imaging (MRI) findings of metaplastic carcinoma. This study evaluates the MRI characteristics and prognostic outcomes across metaplastic carcinoma subtypes. Materials and Methods In this retrospective cohort study, a total of 29 patients with histologically confirmed metaplastic carcinoma from 2011 to 2019 were enrolled. Clinical, pathological, and follow-up data, focusing on disease-free (DFS) and overall survival (OS), are recorded. Breast MRI findings were analyzed and categorized based on BI-RADS 5th edition. Result Among the participants, 19 had squamous carcinoma, 8 had metaplastic carcinoma with mesenchymal differentiation, and 2 had unclassified subtypes. The most common findings were a solitary mass (75.8%), high T2 signal (51.7%), and heterogenous enhancement (65.5%) with a washout kinetic curve (86.2%). The apparent diffusion coefficient (ADC) values in the metaplastic carcinoma with mesenchymal differentiation group were significantly higher (mean 1.83 +/- 0.50 x 10-3 mm2/s) in comparison with the squamous carcinoma group (mean 1.12 +/- 0.21 x 10-3 mm2/s). The cut-off point of the ADC value was 1.53x10-3 mm2/s, with a sensitivity of 71.4% and a specificity of 100% (AUC = 0.937). The five-year DFS and OS rates were 63% and 79% across the board, 78% and 89.5% in the squamous group, and 50% and 53% in the mesenchymal differentiation group, respectively, Conclusion Metaplastic breast carcinoma is a diverse and aggressive malignancy with variable prognosis. Our findings indicate that mesenchymal differentiation is characterized by higher ADC values and correlates with a worse prognosis.